2018
DOI: 10.17240/aibuefd.2018..-396525
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi̇ Öğretmenleri̇n Doğal Matemati̇ksel Di̇l Kullanimlarinin İncelenmesi̇

Abstract: Öğretmenin sınıf ortamında kullandığı matematik dili, çocuklar için matematik girdisidir ve çocukların, okul dönemi boyunca matematik bilgilerinin oluşmasında etkili olmaktadır. Bu çalışmada okul öncesi öğretmenlerinin sınıf ortamında uyguladıkları etkinliklerin incelenmesi ve kullandıkları doğal matematiksel dilinin ortaya çıkarılması amaçlanmıştır. Bu amaçla, Erzurum ili merkezinde bulunan bağımsız anaokulunda tam gün ve yarım gün görev yapan iki öğretmen ile ilkokul bünyesindeki anasınıfında görev yapan bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
1
3
0
2
Order By: Relevance
“…Teachers who will carry out the teaching process of mathematics need sufficient information about content knowledge, pedagogical knowledge, that is, the way of teaching knowledge, and the cognitive development of students during the planning and implementation stages of instruction (Ball et al, 2008;Coddington, 2014;Even, 1993;Shulman, 1987;Yazıcı & Albayrak, 2022). In studies conducted with preschool teachers, it has been observed that teachers have deficiencies about the basic competencies and concepts that preschool mathematics education should incorporate (Aydın, 2009;Chen et al, 2014;Çelik, 2017;Fırat & Dinçer, 2018;Giren & Erdoğan, 2015;Lee & Ginsburg, 2007;Umay, 2003). In the study conducted by Fırat and Dinçer (2018) with preschool teachers, it was determined that teachers did employ a small amount of mathematical conversations in the classroom teaching process.…”
Section: Teacher Training In Pre-school Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers who will carry out the teaching process of mathematics need sufficient information about content knowledge, pedagogical knowledge, that is, the way of teaching knowledge, and the cognitive development of students during the planning and implementation stages of instruction (Ball et al, 2008;Coddington, 2014;Even, 1993;Shulman, 1987;Yazıcı & Albayrak, 2022). In studies conducted with preschool teachers, it has been observed that teachers have deficiencies about the basic competencies and concepts that preschool mathematics education should incorporate (Aydın, 2009;Chen et al, 2014;Çelik, 2017;Fırat & Dinçer, 2018;Giren & Erdoğan, 2015;Lee & Ginsburg, 2007;Umay, 2003). In the study conducted by Fırat and Dinçer (2018) with preschool teachers, it was determined that teachers did employ a small amount of mathematical conversations in the classroom teaching process.…”
Section: Teacher Training In Pre-school Educationmentioning
confidence: 99%
“…In studies conducted with preschool teachers, it has been observed that teachers have deficiencies about the basic competencies and concepts that preschool mathematics education should incorporate (Aydın, 2009;Chen et al, 2014;Çelik, 2017;Fırat & Dinçer, 2018;Giren & Erdoğan, 2015;Lee & Ginsburg, 2007;Umay, 2003). In the study conducted by Fırat and Dinçer (2018) with preschool teachers, it was determined that teachers did employ a small amount of mathematical conversations in the classroom teaching process. In addition, they also found that teachers generally made speeches in the categories of counting, number, and measurement.…”
Section: Teacher Training In Pre-school Educationmentioning
confidence: 99%
“…Bu sonuçlara paralel olarak Pekince ve Avcı (2016) öğretmenlerin planlarında en çok sayma becerisi ile ilgili kavram ve göstergelere yer verdikleri; Baki ve Hacısalihoğlu-Karadeniz (2013) de öğretmenlerin büyük bir kısmının matematik etkinliklerinde daha çok sayma etkinliklerine yer verdiklerini ifade etmişlerdir. Fırat ve Dinçer (2018) okul öncesi öğretmenlerinin sınıf ortamında kullandıkları matematik dilini inceledikleri çalışmalarında, kullanılan ifadelerin en sık sayma/sayı/rakam kavramları olduğunu ortaya koyarak bu sonucu desteklemişlerdir. Orçan-Kaçan ve Halmatov (2017) yaptıkları araştırmalarında öğretmenlerin çoğunluğunun okul öncesinde matematik konularından en çok rakamları tanıma, sayı sayma, nicelikleri karşılaştırma, sayılar ve kavramsal ilişkiler konularına önem verdiklerini ortaya koymuşlardır.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Anadili etkinliklerinde kullanılan öykü, tekerleme ve parmak oyunlarında geçen matematiğe ilişkin unsurların, resimli öykü kitaplarında detaylı bir şekilde ele alınması matematik becerilerinin gelişmesine katkı sağlamaktadır. Türkçe etkinliklerinde matematik hakkında konuşmak, matematiğe özgü kelime ve kavramları kullanmak ve resimlerdeki matematik ile ilgili semboller üzerine çocuğun odaklanmasını sağlamak matematik eğitimi için son derece önemlidir (Fırat ve Dinçer, 2018). Hong'a (1996) göre resimli öykü kitaplarının temel amacı matematiği öğretmek değildir ancak kitapların içerisinde geçen matematik unsurlarının farkına varılmasıyla matematik ile ilgili düşünmenin temelleri atılır.…”
Section: Introductionunclassified
“…These mathematical concepts, which are used in mother tongue activities in story, rhymes and finger games and the elaboration of these concepts in story books contribute to the development of mathematical skills. Talking about mathematics in Turkish activities, using mathematical words and concepts and providing the focus of the child on the symbols related to mathematics in the pictures are extremely important for mathematics education (Fırat & Dinçer, 2018).…”
Section: Introductionmentioning
confidence: 99%